Design of Fe7S8@Lip Composite for the pH-Selective and Magnetically Targeted Programmed Release of H2S - Shenghua Wang; Hanlin Wei; Jialian Li; Ning Liu; Zhiming Deng; Junqing Huang (Magnetochemistry)
The significance of hydrogen sulfide (H2S) release in vivo is multifaceted. It functions as a crucial gaseous signaling molecule with extensive physiological and pathological impacts within organisms. To create novel H2S-releasing materials, we synthesized Fe7S8@Lip, a slow-release gas nanocomposite, which exhibits stable and sustained H2S-release properties. Our gas releaser possesses selective H2S-release capabilities, and, notably, it can achieve effective H2S release under magnetic force with the assistance of a magnetic field. In conclusion, our findings indicate that Fe7S8@Lip can serve as an H2S slow-release nanocomposite, offering a potentially innovative approach for programmed H2S release in vivo.